Violence and exodus in Kenya's Rift Valley, 2008: predictable and preventable? - Anderson, D; Lochery, E (Taylor and Francis, 2008)
This article offers a preliminary analysis of the outbreak of violence in the Rift Valley Province of Kenya, over January and February 2008, following the national elections of December 2007. Maps of the earliest phase of the violence are reproduced to illustrate the sequencing and location of conflict. The causes of the violence are explored through discussion of historical patterns of land settlement in the Rift Valley, the impact of political violence in key constituencies since the early 1990s, and more recent political contingencies around the question of constitutional reform and regionalism (majimboism). The violence of 2008 bore strong similarities to earlier episodes of conflict in the Rift Valley, and in that sense was predictable and might have been prevented. Though the December 2007 poll was the catalyst for this violence, its causes are to be found in deeper-rooted historical and political conflicts.